2020
DOI: 10.1093/jcag/gwz044
|View full text |Cite
|
Sign up to set email alerts
|

The Argument Against a Biosimilar Switch Policy for Infliximab in Patients with Inflammatory Bowel Disease Living in Alberta

Abstract: A nonmedical switch policy is currently being considered in Alberta, which would force patients on originator biologics to biosimilar alternatives with the hypothetical aim of reducing costs to the health care system. The evidence to support the safety of nonmedical switching in patients with inflammatory bowel disease (IBD) is of low to very low quality; in fact, existing data suggest a potential risk of harm. In a pooled analysis of randomized controlled trials, one patient would lose response to infliximab … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…Another recent review of 178 switching studies also concluded that for the products studied, a single switch is not intrinsically linked to an increase in immunogenicity, safety, or efficacy issues [ 37 ]. Nonetheless, the “fact” that there is a supposed controversy about the practice of switching from a reference biologic to a biosimilar was cited by another publication as part of a set of arguments against a Canadian provincial policy of switching from reference infliximab to biosimilar infliximab [ 38 ]. There is no scientific controversy about the practice of switching [ 39 ], but the false narrative persists.…”
Section: Types Of Biosimilar Disparagement and Misinformationmentioning
confidence: 99%
See 1 more Smart Citation
“…Another recent review of 178 switching studies also concluded that for the products studied, a single switch is not intrinsically linked to an increase in immunogenicity, safety, or efficacy issues [ 37 ]. Nonetheless, the “fact” that there is a supposed controversy about the practice of switching from a reference biologic to a biosimilar was cited by another publication as part of a set of arguments against a Canadian provincial policy of switching from reference infliximab to biosimilar infliximab [ 38 ]. There is no scientific controversy about the practice of switching [ 39 ], but the false narrative persists.…”
Section: Types Of Biosimilar Disparagement and Misinformationmentioning
confidence: 99%
“…Another example of negative framing is the pervasive use of the term “non-medical switching” or “non-medical substitution” when describing the transition from reference product to a biosimilar. This phrase has been used by both publications that support this practice as well as by those that warn against it [ 38 , 45 ]. However, the terms non-medical switching and non-medical substitution actually refer to formulary-driven changes between drug options that are thought to be therapeutically equivalent, but that are very different in structure [ 46 ].…”
Section: Types Of Biosimilar Disparagement and Misinformationmentioning
confidence: 99%
“…16 Our findings of differences between clinical indications may also reflect perceived policy gaps from the perspectives of those affected by policy change and a need for stronger engagement and collaboration with stakeholders. 7,19 With the complexity of using biologics, there has been greater integration of patient support programs into clinical practice; in this regard, innovator biologics typically have well-established support programs with large number of infusion centers, making them more accessible and convenient to patients in more remote geographic areas or during evenings and weekends. 11,19 This may affect infliximab more, since it has an intravenous route of delivery versus the subcutaneous route for etanercept.…”
Section: Figurementioning
confidence: 99%
“…7,19 With the complexity of using biologics, there has been greater integration of patient support programs into clinical practice; in this regard, innovator biologics typically have well-established support programs with large number of infusion centers, making them more accessible and convenient to patients in more remote geographic areas or during evenings and weekends. 11,19 This may affect infliximab more, since it has an intravenous route of delivery versus the subcutaneous route for etanercept. 23 Improving consideration of factors associated with biologic administration and patient care can positively affect the quality of care associated with biosimilars and enhance the success of the policy approach.…”
Section: Figurementioning
confidence: 99%
“…Significant heterogeneity among existing observational studies limits their interpretation as well. Further, while non-medical switching policies have been enacted, there has been incomplete pharmacovigilance reporting on the patient level and pharmacoepidemiologic evaluation at the population level [11]. Lastly, since the available data pertain to single switches from originator compound to CT-P13, they incompletely reflect the multi-directional switching that may occur in practice with non-medical switching.…”
mentioning
confidence: 99%